SOSIALISASI DAN PELATIHAN PENGELOLAAN SAMPAH RAMAH LINGKUNGAN BAGI PELAKU USAHA DI KOTA MAKASSAR - Mohamad Ikbal Riski A. Danial; Cicilia Selry Tanri; Abdul Mun'im Thariq; Andi Khairunnisa Salsabila Putri; Syam S. Kumaji; Rika Wahyuni Rusti Annisa (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
The problem of urban waste in Makassar City continues to increase in line with economic growth and the number of businesses, particularly micro, small, and medium enterprises (MSMEs). The low level of knowledge and skills among business actors in environmentally friendly waste management means that waste is not yet being managed optimally and still has the potential to cause negative impacts on the environment. The community service activity aims to provide standards for the implementation of waste reduction and management at the source, based on Presidential Regulation No. 97 of 2017 concerning national policies and strategies for the management of household waste and similar waste, as well as to increase the knowledge, attitudes, and skills of business actors in Makassar City in managing waste in an environmentally friendly manner through socialization and training activities. The methods used to carry out these activities are socialization, training, and discussions on environmentally friendly waste management. The activities were carried out in a participatory manner through material delivery, interactive discussions, and hands-on practice. The results of the activities show an increase in business actors' understanding of the importance of environmentally friendly waste management and their ability to implement waste sorting and management practices at the source. It is hoped that this activity will encourage changes in the behavior of business actors in waste management, reduce the amount of waste sent to final processing sites (landfills), and support the realization of a clean and sustainable environment in the city of Makassar.